Pengaruh Pemberian Biji Labu Kuning Terhadap Peningkatan Kadar Hemoglobin - Cakrawati.R, Cakrawati.R; Sumarni, Sri; Sudiyono, Sudiyono (Universitas Malahayati, 2024)
ABSTRACT Iron Deficiency Anemia is anemia caused by a lack of iron availability in the body. Hemoglobin is a protein found in human erythrocytes. Deficiency in hemoglobin levels is influenced by insufficient iron in the body and the iron metabolism process. Anemia is declared if the hemoglobin level is below normal levels. Nutrients that play an important role in the formation and function of hemoglobin are Iron, Protein, Vitamin C. Pumpkin seeds contain many nutrients that are beneficial for body health such as phytochemicals (phytosterols), vitamin C, vitamin E, beta-carotene and minerals (magnesium, selenium and zinc). Pumpkin seeds also contain fiber which inhibits cholesterol absorption in the intestine. Pumpkin seeds contain various important nutrients, including iron, zinc, magnesium, and omega-6 and omega-3 fats. This study aims to determine the effect of giving pumpkin seeds on increasing hemoglobin levels. Study of literature by collecting relevant literature using online journal data based on, Researchgate, Google Scholar, PubMed and Garuda identified in 2013 -2023. The results of the analysis showed that giving pumpkin seeds had an impact on increasing hemoglobin levels. Conclusion: Giving pumpkin seeds to teenagers, women of childbearing age and pregnant women can increase hemoglobin levels and prevent iron deficiency anemia. Keywords: Anemia, Pumpkin Seeds, Hemoglobin ABSTRAK Anemia Defisiensi Besi adalah anemia yang disebabkan oleh kurangnya ketersediaan zat besi dalam tubuh. Hemoglobin merupakan protein yang terdapat dalam eritrosit manusia, Kekurangan kadar hemoglobin dipengaruhi oleh tercukupinya zat besi dalam tubuh dan proses metabolisme besi. Dinyatakan anemia apabila kadar hemoglobin di bawah kadar normal. Zat gizi yang berperan penting dalam pembentukan dan fungsi hemoglobin yaitu Zat Besi, Protein, Vitamin C. Biji labu kuning mengandung banyak nutrisi yang bermanfaat bagi kesehatan tubuh seperti fitokimia (fitosterol), vitamin C, vitamin E, betakaroten dan mineral (magnesium, selenium dan zinc). Biji labu kuning juga mengandung serat yang menghambat penyerapan kolesterol di usus. Biji labu mengandung berbagai nutrisi penting, termasuk zat besi, seng, magnesium, serta lemak omega-6 dan omega-3. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian biji labu kuning terhadap peningkatan kadar hemoglobin. Studi literatur dengan mengumpulkan literatur yang relevan dengan menggunakan data jurnal online berdasarkan Researchgate, Google Scholar, PubMed and Garuda yang diidentifikasi tahun 2013 -2023. Hasil analisis menunjukkan bahwa pemberian biji labu kuning berdampak pada peningkatan kadar hemoglobin. Kesimpulan Pemberian biji labu kuning pada remaja, wanita usia subur dan ibu hamil dapat meningkatkan kadar hemoglobin dan dapat mencegah anemia defisiensi besi. Kata Kunci: Anemia, Biji Labu Kuning, Hemoglobin